ANALISIS KETERLIBATAN PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH DI PROVINSI SUMATERA UTARA - Annisa Fitri Awaliyah; Wan Shalah Sabila (CV. ADIBA AISHA AMIRA, 2024)
This research examines the relationship between local revenue and regional taxes in North Sumatra Province from 2018 to 2021. The quantitative study was conducted from 2018 to FY 2021 using data from the provincial government, environmental engineering government/city, journals, scientific publications, literature reviews on research problems, and other sources. The results of the analysis show that although district and city regional taxes in North Sumatra do contribute to local original income, this contribution gradually decreases from 2018 to 2021. However, the realization of regional income in the first sector shows an increase. Income afterward. the effect on first income is only slight. Initial income generation in the regions always represents an increase in income so that it does not have a significant impact on the initial income of the community determined by the regional government. Based on the research, the above results were obtained, namely the level of tax implementation, main regional income and taxes in relation to the 2018–2021 budget targets set by regional government in the district and city provinces of North Sumatra